2021
DOI: 10.18287/2412-6179-co-859
|View full text |Cite
|
Sign up to set email alerts
|

Road images augmentation with synthetic traffic signs using neural networks

Abstract: Traffic sign recognition is a well-researched problem in computer vision. However, the state of the art methods works only for frequent sign classes, which are well represented in training datasets. We consider the task of rare traffic sign detection and classification. We aim to solve that problem by using synthetic training data. Such training data is obtained by embedding synthetic images of signs in the real photos. We propose three methods for making synthetic signs consistent with a scene in appearance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(41 reference statements)
0
5
0
1
Order By: Relevance
“…For traffic sign detector, we have found that modeling the context in which traffic signs occur is more important than modeling the traffic signs themselves [ 43 ]. We conducted experiments with basic methods for inserting a sign image onto the original image of an unsigned road (the basic methods do not take into account the context of a traffic sign): CGI —samples were obtained by rendering three-dimensional models of traffic signs on pillars in real road images.…”
Section: Validation and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For traffic sign detector, we have found that modeling the context in which traffic signs occur is more important than modeling the traffic signs themselves [ 43 ]. We conducted experiments with basic methods for inserting a sign image onto the original image of an unsigned road (the basic methods do not take into account the context of a traffic sign): CGI —samples were obtained by rendering three-dimensional models of traffic signs on pillars in real road images.…”
Section: Validation and Resultsmentioning
confidence: 99%
“…Pasted —In this approach we trained together neural networks for inpainting and processing of embedded traffic sign [ 43 ].…”
Section: Validation and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Теоретически можно генерировать бесконечное количество обучающих изображений с большими вариациями, где разметка осуществляется автоматически. Процесс генерирования данных называют аугментацией [3]. Обучение с искусственными образцами позволяет точно контролировать рендеринг изображений и, следовательно, различные свойства набора данных [4].…”
Section: Introductionunclassified